Changes in stride pattern of elite women's 400 metres hurdles from 2019 to 2022: an analysis by performance level - Casal-García, N.; López-Del Amo, J. L. (Frontiers in Sports and Active Living, 2025)
Introduction: The main objective of this study was to investigate the stride patterns of elite women's 400 m hurdles which have undergone significant evolution in recent years, resulting in a complete change in the stride patterns of the athletes.